2014
DOI: 10.5772/58400
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Fin-Ray Trajectory Tracking of Bio-Inspired Robotic Undulating Fins via an Experimental-Numerical Approach

Abstract: In the past decade, biomimetic undulating fin propulsion has been one of the main topics considered by scientists and researchers in the field of robotic fish. This technology is inspired by the biological wave-like propulsion of ribbon-finned fish. The swimming modes have aquatic application potentials with greater manoeuvrability, less detectable noise or wake and better efficiency at low speeds. The present work concentrates on the evaluation of fin-ray trajectory tracking of biorobotic undulating fins at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The robot could generate arbitrary undulating waveforms and kinematic analyses were also performed. Hu and his colleagues studied the locomotion mechanism of bio-inspired robotic undulating fins by carrying out biological measurements [25], establishing kinematic equations, computational fluid dynamics (CFD) analyses [26], trajectory tracking of the fin's motion [27], and experimental analyses of the robot propelled by undulating fins. These works showed that the undulating fins based on the Gymnarchus niloticus could move forward, backward, or turn around underwater with good propulsive efficiency and high maneuverability.…”
Section: Introductionmentioning
confidence: 99%
“…The robot could generate arbitrary undulating waveforms and kinematic analyses were also performed. Hu and his colleagues studied the locomotion mechanism of bio-inspired robotic undulating fins by carrying out biological measurements [25], establishing kinematic equations, computational fluid dynamics (CFD) analyses [26], trajectory tracking of the fin's motion [27], and experimental analyses of the robot propelled by undulating fins. These works showed that the undulating fins based on the Gymnarchus niloticus could move forward, backward, or turn around underwater with good propulsive efficiency and high maneuverability.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned inconsistency does exist and has prevented robotic fish models from replicating the locomotion or behaviours of their biological counterparts. An experimental-numerical approach was employed to reveal that the tracking inconsistency is jointly caused by hysteresis nonlinearity from hydrodynamics and the elastic effect of the membrane [12,13]. Significantly, some bio-inspired joints or components are driven by smart materials that possess an inherent feature of hysteresis nonlinearity.…”
Section: Control Problem Of Reproducing Animal Locomotionmentioning
confidence: 99%
“…The advantages of fin actuators are noiselessness, possibility of moving backward, for example, by creating a wave motion [54], increased efficiency at low speeds, and high stability while holding attitude [36]. There is a variety of underwater robots' motion strategies that use different fin designs copied from fish, such as modifiable configuration of robot surface [51].…”
Section: Introductionmentioning
confidence: 99%
“…Effective use of the environment properties. For example, flying amphibian robots' multicopters and planes can be applied for motion in two environments [36]. Energy demanding flight and periodic ground motion can be combined for surface locomotion [37,38].…”
Section: Introductionmentioning
confidence: 99%